Experimental investigation of heat transfer and dehumidifying performance of novel condensing panel - Koca, Aliihsan; Atayilmaz, S. Ozgur; Agra, Ozden (ELSEVIER SCIENCE SA, 2016)
In this study, we propose a novel cooling and dehumidification strategy, in which a condensing panel can be hydronically connected in series with the radiant cooling system to overcome condensation,risks. According to the concept, the sensible load is primarily treated by radiant cooling panels and the latent load and some amount of sensible load can be accomplished by the condensing panel. This paper evaluates the heat transfer and dehumidifying performance of the proposed condensing panel. For these purposes, a new experimental set-up was developed and condensation heat transfer of water vapor in the presence of air, on a vertical surface with different sub-cooling temperatures studied experimentally. However, the new test set-up allowed the measurement of the heat transfer coefficient from the measurement of the total sensible, radiation and condensation heat flux densities and the characteristic temperature differences. To investigate the heat transfer coefficient, tests were conducted using surface temperatures of 10.6, 10.9,11.4, 12.2, 13 and 14 degrees C with the same initial conditions of mixture (mixture temperature 25 degrees C and relative humidity 75%). The average heat transfer coefficients were determined using the characteristic temperatures. The approximate average values 2.21,4.45, 3.24 and 6.69 W m(-2) K-1 were found respectively for the radiation, convection, condensation and total sensible heat transfer coefficients. The present experimental data provide a new database for the natural convective steam condensation in the presence of non-condensable gas over the vertical plate for the full scale atmospheric condition in a closed room. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Condensation; Condensing panel; Radiant cooling; Heat transfer coefficient; FLOOR NUSSELT NUMBER; TRANSFER COEFFICIENTS; NATURAL-CONVECTION; CEILING PANEL; SURFACE RADIATION; COOLING CAPACITY; THERMAL COMFORT; ENERGY; SYSTEM; Construction & Building Technology; Energy & Fuels; Engineering